Shear performance of concrete slab with the addition of oil palm shell as lightweight concrete aggregate - Wan Nur Hafieza, Wan Mat (2015)
This thesis deals with the use of waste materials, oil palm shell (OPS) as a replacement for coarse aggregate in the concrete. The objectives of this thesis are to determine the potential of OPS as a coarse aggregate replacement in lightweight concrete and to study the structural behaviour of slab with the addition of OPS. The potential of palm oil byproduct, OPS to be used as a replacement of coarse aggregates in the concrete production can be guaranteed. As the cost of raw materials in the concrete industry is getting higher therefore manipulating the waste material is the best way to lessen the cost of concrete. The utilization of OPS in the concrete also helps to solve environmental problem caused by the improper disposal of waste materials. The addition of OPS as a replacement to coarse aggregate produces lightweight concrete which is a very cost effective. The paper reports on the experimental works on the structural behaviour of concrete slab with the addition of OPS. This thesis describes the tests which are to be applied on concrete which are compression test and combined bending and shear test. Concrete specimens involved in this research are cube of size 100 mm × 100 mm × 100 mm and slab of size 350 mm × 500 mm × 100 mm.Three different concrete mix compositions were prepared which were the concrete without the addition of OPS (batch 1, B1), concrete with the addition of 50% OPS (batch 2, B2) and concrete with the addition of 100% OPS (batch 3, B3). The compressive strength of cube specimens was carried out at 7 and 28 days. The results show that the increase in percentage replacement of OPS decreased the compressive strength. Concrete slab specimens were tested at 28 days to observe the failure under the shear load. The results showed that increasing the content of OPS into the concrete slab gives no significant effect to the shear failure load improvement.